2023
DOI: 10.1007/s00415-023-11617-1
|View full text |Cite
|
Sign up to set email alerts
|

Ravulizumab pharmacokinetics and pharmacodynamics in patients with generalized myasthenia gravis

Abstract: Introduction The terminal complement C5 inhibitor ravulizumab has a long elimination half-life, allowing maintenance dosing every 8 weeks. In the 26-week, double-blind, randomized, placebo-controlled period (RCP) of the CHAMPION MG study, ravulizumab provided rapid and sustained efficacy and was well tolerated in adults with anti-acetylcholine receptor antibody-positive (AChR Ab+) generalized myasthenia gravis (gMG). This analysis evaluated the pharmacokinetics (PK), pharmacodynamics (PD), and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Pharmacokinetic and pharmacodynamic profiles similar to those reported here were observed in studies in patients with atypical hemolytic uremic syndrome, generalized myasthenia gravis, and paroxysmal nocturnal hemoglobinuria ( 13 , 20 , 21 ). The immediate, complete, and sustained suppression of C5 after ravulizumab administration may account for the adjudicated on-trial relapse risk reduction as observed in the CHAMPION-NMOSD trial ( 14 ).…”
Section: Discussionsupporting
confidence: 84%
“…Pharmacokinetic and pharmacodynamic profiles similar to those reported here were observed in studies in patients with atypical hemolytic uremic syndrome, generalized myasthenia gravis, and paroxysmal nocturnal hemoglobinuria ( 13 , 20 , 21 ). The immediate, complete, and sustained suppression of C5 after ravulizumab administration may account for the adjudicated on-trial relapse risk reduction as observed in the CHAMPION-NMOSD trial ( 14 ).…”
Section: Discussionsupporting
confidence: 84%
“…Ravulizumab is a monoclonal antibody complement inhibitor approved by the Food and Drug Administration (FDA) in April 2022 for AChR-Ab-generalized MG. A phase 3, randomized, double-blind, placebo-controlled, multicenter trial in patients with AChR-Ab-generalized MG indicated improved clinical outcomes for patients treated with ravulizumab, and the drug was well tolerated ( 41 ). The latest pharmacokinetics and pharmacodynamics research based on the data from this phase 3 study supports dosing every 8 weeks for immediate, complete, and sustained inhibition of terminal complement C5, and it could reduce the burden on patients ( 42 ).…”
Section: Discussionmentioning
confidence: 88%
“…In the EU and UK, several health authorities will soon assess new treatments for gMG (including efgartigimod and ravulizumab) in terms of their value for money, with MG-ADL as the primary clinical trial endpoint [21,27]. Analyses including the one presented in the current study are needed to capture the clinical and economic facets of treatment comprehensively and accurately for two major reasons.…”
Section: Discussionmentioning
confidence: 99%